Classification of Patient Portals Described in Evaluation Studies Using the TOPCOP Taxonomy - Leb, Ines; Magnin, Selina; Boeker, Martin; Prokosch, Hans-Ulrich; Ammenwerth, Elske; Glöggler, Michael (Healthcare of the Future 2022, 2022)
Many patient portals have been introduced and evaluated in recent years. The results of evaluation studies are difficult to compare, however, as the evaluated patient portal is often not clearly or only incompletely described in the publication. This problem is common to evaluations in health informatics. We evaluated the completeness of descriptions of patient portals in 15 exemplary evaluation publications using the TOPCOP taxonomy. Our results show that core functionalities such as portal design, patient communication, educational features, or system notifications were quite clearly described in all 15 evaluation studies. Other descriptions, such as web accessibility or data management, were often not provided. We conclude that taxonomies such as TOPCOP should be used and even required for describing interventions in evaluation papers.
CRIS-Team Scopus Importer:2022-05-27
Keywords: evaluation; health informatics; information management; Patient portal; taxonomy